Nitrogen uptake in relation to excess supply and its effects on the lichens Evernia prunastri (L.) Ach and Xanthoria parietina (L.) Th. Fr. - Gaio-Oliveira, Gisela (2011)
ACESSO via B-on: http://dx.doi.org/10.1007/s00425-004-1396-1